GLOBAL PROBLEMS - Toyeva Gulchiroy To'lqinjon qizi (TADQIQOTLAR, 2025)
This article discusses the most pressing global issues in the modern world, their causes,  and  consequences.  Problems  such  as  climate  change,  environmental degradation,  poverty,  hunger,  wars,  pandemics,  and  human  rights  violations  pose serious threats to all of humanity. Addressing these challenges requires international cooperation,  sustainable  development  policies,  and  increased  environmental awareness.